Full or Empty Mode: The Organization of the Full or Empty Spaces on the Covers of the Singles of Depeche Mode between the Years of 1981 and 1998 (Global Journal of Human-Social Science, 2017)
Music as an art form based on sound and silence recorded as actual sounds since the second half of the 19th century and developed in time according to the technical improvements. Covers both protecting and labeling recording mediums are graphic design spaces to organize. The pre-production design of 2 dimensional printed surfaces called the graphic design. Like every design field graphic design has its own elements and principles as guides. The aim of this paper is to analyze the full and empty space organizations on the covers of the Depeche Mode Singles 81-98 Set. Depeche Mode is a synth pop, new wave, electronic and dance rock and alternative rock band established in 1980 and still active. Depeche Mode has 31 times nominated and 10 times won the highly prestigious worldwide prizes during those years, it is the most popular electronic band the world has ever known and in the list of the 50 bands that changed the world. In the Singles 81-98 Set there are totally 36 covers which grouped as 6 packages each consisting 6 covers. In this paper 6 of the 36 covers have analyzed according to the 6 main graphic design principles. On the 6 cover the full and empty spaces organized according to the 6 main principles to create an extraordinary effect which is consistent to the music in them.
Keywords: graphic design; cover design; depeche mode; design; music album